Failure pattern and survival after breast conserving therapy. Long-term results of the Danish Breast Cancer Group (DBCG) 89 TM cohort. (2nd August 2016) - Lyngholm, C. D.; Laurberg, T.; Alsner, J.; Damsgaard, T. E.; Overgaard, J.; Christiansen, P. M.
Abstract: Based on the results from the DBCG 82 trial, breast conserving therapy (BCT) has been implemented as standard in Denmark since 1989, and today constitutes more than 70% of the primary treatment. Our aim was to evaluate the implementation of BCT as a routine procedure in patients treated according to the DBCG 89 program and compare recurrence pattern and survival both overall and when separated in age groups, with the results from the randomized DBCG 82 TM trial.Material and methods : A total of 1847 patients treated between 1989 and 1999 were included in a retrospective population-based cohort study. Data from the DBCG database were completed via search through the Danish Pathology Data Bank and medical records.Results : Median follow-up time was 17 years. At 20 years the cumulative incidences of local recurrence (LR) and disease-specific mortality (DSM) were 15.3% and 25.8%, respectively. Twenty-year overall survival (OS) and recurrence-free survival were 63.7% and 43.1%, respectively. Subdivided by age groups cumulative incidences at 20 years were LR: 18.9%, 10.5% and 12.4%, and DSM: 28.9%, 18.9% and 28.4% in young (≤45 years), middle-aged (46–55 years) and older (≥56 years) women, respectively. In an adjusted analysis age maintained a significant and independent effect on both LR and DSM.Conclusion : The DBCG 82 TM program was successfully implemented. The women treated with BCT in the DBCG 89 program displayed equal failure pattern and improved survival in comparison with women from the DBCG 82 TM protocol. Occurrence of first failure and mortality varied with age; demonstrated by increased risk of LR, DM and DSM in the young patients and increased risk of DM and DSM in the older patients, compared to the middle-aged patients.